Enlargement and the European geography of the information technology sector - Frank Barry; Declan Curran (University College Dublin, Department of Economics, 2004)
The information technology sector in Europe, comprising the production of computer hardware and software, is disproportionately located on the continent's western periphery. The vast bulk of computers sold in Europe in the 1990s were assembled either in Ireland or Scotland, while Ireland also accounted for over 40 percent of all packaged software and 60 percent of all business software sold in Europe. As the sector in both these locations is largely foreign owned, the question arises as to whether EU enlargement might impact on the geography of the sector by diverting information technology FDI from the western to the new eastern periphery. This issue is explored in the present paper by analysis of five individual sub-segments: computer assembly and electronic components, R&D, mass market packaged software and the remainder of the software sector.
hdl:10197/1264
Keywords: 330; EU-Erweiterung; Computerindustrie; Softwareindustrie; Industriegeographie; Osteuropa; EU-Staaten